Analysis of the Fusion of Mathematical Modeling Thoughts Based on Computer Technology and Teaching Practice in Colleges and Universities - Song, Xueli (Journal of physics. Conference series, 2020)
High mathematics is the most important course in college mathematics, which is one of the subjects with the highest proportion of College Students' credits. However, mathematical modeling is a method to solve practical problems with models, which has been widely used to solve a variety of practical problems, including economy, industry, medicine, society and so on. With the development of computer technology, we can use a variety of effective computer modeling software for complex mathematical modeling, such as MATLAB, one of the most common mathematical modeling software. Therefore, colleges and universities must actively use computer technology, integrate the idea of mathematical modeling into mathematical practice, which can better integrate mathematical resources and teaching media. By constantly improving the way of mathematics learning, college students will better improve the efficiency of mathematics learning, which can also improve students' thinking consciousness of applying mathematics to work. First of all, this paper analyzes the important role of mathematical modeling based on computer technology in mathematical practice. Then, this paper puts forward some questions. Finally, some suggestions are put forward.